Giuliani : the rise and tragic fall of America's mayor - Kirtzman, Andrew (Simon & Schuster, 2022)
In this revealing biography, Andrew Kirtzman pieces together Giuliani's rise and fall from hundreds of interviews with friends, family members, White House officials, business partners, and close confidants, some of whom have never gone on the record before. He reveals new information about Giuliani₂s role in the 2020 election debacle, his relationship with Trump, his troubled personal life, and much more.